Analysis of Employee Performance Based on Compensation, Workload, and Work Discipline (Study on Employees of PT. Vasa Sukses Mandiri) - Fakhriyyah, Davina Ayu; Prabowo, Budi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine how the effect of compensation (X1), workload (X2), and work discipline (X3), on employee performance (Y) at PT Vasa Sukses Mandiri. This type of research uses associative research using a quantitative approach. The population in this study were employees of Pt. Vasa Sukses Mandiri, while the number of samples used was 48 respondents using probability sampling. The data analysis tools used in this study are validity test, classical assumption test, multiple regression linear regression analysis. The results of this study indicate that based on the partial test (1) Compensation has a positive effect on employee performance Pt. Vasa Sukses Mandiri; (2) Workload has a positive effect on employee performance Pt. Vasa Sukses Mandiri; (3) Work Discipline has a positive effect on employee performance Pt. Vasa Sukses Mandiri. (4) Compensation, Workload and Work Discipline simultaneously have a significant effect on the performance of employees of Pt. Vasa Sukses Mandiri. Of the 4 dominant variables is work discipline, this can be seen based on the highest multiple linear regression value of 0.395.